Determinants of exercise intolerance in elderly heart failure patients with preserved ejection fraction - Haykowsky, Mark J; Brubaker, Peter H; John, Jerry M; Stewart, Kathryn P; Morgan, Timothy M; Kitzman, Dalane W (Journal of the American College of Cardiology, 2011)
The purpose of this study was to determine the mechanisms responsible for reduced aerobic capacity (peak Vo(2)) in patients with heart failure with preserved ejection fraction (HFPEF). HFPEF is the predominant form of heart failure in older persons. Exercise intolerance is the primary symptom among patients with HFPEF and a major determinant of reduced quality of life. In contrast to patients with heart failure and reduced ejection fraction, the mechanism of exercise intolerance in HFPEF is less well understood. Left ventricular volumes (2-dimensional echocardiography), cardiac output, Vo(2), and calculated arterial-venous oxygen content difference (A-Vo(2) Diff) were measured at rest and during incremental, exhaustive upright cycle exercise in 48 HFPEF patients (age 69 ± 6 years) and 25 healthy age-matched controls. In HFPEF patients compared with healthy controls, Vo(2) was reduced at peak exercise (14.3 ± 0.5 ml·kg·min(-1) vs. 20.4 ± 0.6 ml·kg·min(-1); p < 0.0001) and was associated with a reduced peak cardiac output (6.3 ± 0.2 l·min(-1) vs. 7.6 ± 0.2 l·min(-1); p < 0.0001) and A-Vo(2) Diff (17 ± 0.4 ml·dl(-1) vs. 19 ± 0.4 ml·dl(-1), p < 0.0007). The strongest independent predictor of peak Vo(2) was the change in A-Vo(2) Diff from rest to peak exercise (A-Vo(2) Diff reserve) for both HFPEF patients (partial correlate, 0.58; standardized β coefficient, 0.66; p = 0.0002) and healthy controls (partial correlate, 0.61; standardized β coefficient, 0.41; p = 0.005). Both reduced cardiac output and A-Vo(2) Diff contribute significantly to the severe exercise intolerance in elderly HFPEF patients. The finding that A-Vo(2) Diff reserve is an independent predictor of peak Vo(2) suggests that peripheral, noncardiac factors are important contributors to exercise intolerance in these patients.